2018
DOI: 10.1002/ijc.31297
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the CXCL12/CXCR4 pathway and myeloid cells to improve radiation treatment of locally advanced cervical cancer

Abstract: Cervical cancer is the fourth most commonly diagnosed cancer and the fourth leading cause of cancer death in women worldwide. Approximately half of cervical cancer patients present with locally advanced disease, for which surgery is not an option. These cases are nonetheless potentially curable with radiotherapy and cisplatin chemotherapy. Unfortunately, some tumours are resistant to treatment, and lymph node and distant recurrences are major problems in patients with advanced disease at diagnosis. New targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 149 publications
(204 reference statements)
0
32
0
Order By: Relevance
“…Testable compounds can be directly added to small volumes of medium, and skeletal defects can be efficiently analyzed by live imaging in the translucent larvae ( 50 ). In the past, several chemical inhibitors for chemokine receptors have been developed and clinically tested, especially in the context of cancer, immune deficiencies, and inflammation ( 51 53 ). These include inhibitors for CXCR3 ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Testable compounds can be directly added to small volumes of medium, and skeletal defects can be efficiently analyzed by live imaging in the translucent larvae ( 50 ). In the past, several chemical inhibitors for chemokine receptors have been developed and clinically tested, especially in the context of cancer, immune deficiencies, and inflammation ( 51 53 ). These include inhibitors for CXCR3 ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drug sensitivity is an important prognostic factor for GC patients. Previous studies indicated that CXCR4 overexpression could protect tumor cells from chemotherapy drugs [48,49]. The 17‐agg drug is an HSP90 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, maraviroc blocks the CCR5 receptor, which also improves PAH 24 . On the other hand, blocking CXCR4 has been useful in experimental PAH and promising in cancer 80,81 but its side effects still preclude its clinical use 82 . Therefore, HIV effects mediated by the CXCR4 pathway still remain largely unapproached by current antiretroviral drug strategies.…”
Section: Discussionmentioning
confidence: 99%